1990
DOI: 10.1002/jnr.490250211
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of chemically induced synaptosomal changes

Abstract: The ability of altered environmental conditions to modulate some properties of synaptosomes has been studied. Incubation conditions used included the presence of methyl mercury or an organochlorine insecticide: chlordecone. Other adverse chemical conditions during incubation were the absence of calcium salts from the incubation medium or the addition of agents bringing about enhanced oxidative conditions. Synaptosomal parameters studied were the cytosolic level of free, ionic calcium, [Ca2+]i, the extent of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
1

Year Published

1990
1990
1995
1995

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 33 publications
2
22
1
Order By: Relevance
“…Studies have reported that MeHg 1 This work was supported by NIH Grants ES 04071 and ES 07157. 161 stimulates lipid peroxidation (Yonaha et al, 1983) and the lipoperoxidative effects of MeHg are mitigated by the antioxidant a-tocopherol (vitamin E; Halliwell and Gutteridge, 1985;Kasuya, 1975;Bondy and McKee, 1990). Additionally, this laboratory has recently demonstrated that both in vivo and in vitro exposures to MeHg increased the formation rate of reactive oxygen species in mouse brain , effects that were observed only in the cerebellum, the brain region believed to be selectively vulnerable to MeHg (Syverson et al, 1981 ).…”
mentioning
confidence: 99%
“…Studies have reported that MeHg 1 This work was supported by NIH Grants ES 04071 and ES 07157. 161 stimulates lipid peroxidation (Yonaha et al, 1983) and the lipoperoxidative effects of MeHg are mitigated by the antioxidant a-tocopherol (vitamin E; Halliwell and Gutteridge, 1985;Kasuya, 1975;Bondy and McKee, 1990). Additionally, this laboratory has recently demonstrated that both in vivo and in vitro exposures to MeHg increased the formation rate of reactive oxygen species in mouse brain , effects that were observed only in the cerebellum, the brain region believed to be selectively vulnerable to MeHg (Syverson et al, 1981 ).…”
mentioning
confidence: 99%
“…Recently, ROS have been reported to play a role in the neurotoxic mechanisms of methylmercury and trimethyltin [17, :j:]. These studies were performed using the fluorescent dyes 2' ,7'-dichlorofluorescein and rhodamine 123, markers that have proven to be more sensitive measures of oxidative stress than the traditional thiobarbituric acid assay [17,18]. A ferryl-ion or peroxo-metal complex may be the reactive species directly responsible for the oxidation of nonfluorescent dichlorofluorescin to highly fluorescent dichlorofluorescein [19].…”
mentioning
confidence: 99%
“…Ganglioside GM!, a membrane-stabilizing agent effective within the CNS, may also mitigate some components of oxidative damage to neural tissue. This ganglioside has been reported protective against ischemia (Mahadik et al, 1989), edema (Koga et al, 1990, Skaper et al, 1989, and direct oxidative activity (Bondy and McKee, 1990). The therapeutic application of macromolecular proteins as a means of reducing ROS production is obviously somewhat limited.…”
Section: Mitigation Of Cerebral Oxidative Stressmentioning
confidence: 99%